Doses e modos de aplicação de boro na produção de mudas de nespereira - Penha, Estevan Teodoro Santana [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The loquat cultivation is increasing in Brazil and in the world and is an important source of income for small farms, however, the production of seedlings can be an obstacle to its expansion. Thus the aim of this study was to evaluate Boron reflection on the quality of loquat seedlings, and the place of supply to plants parent by determining the most effective application method in this process. There were four boron doses (0, 2.5, 5.0 and 7.5 mg dm-3) and two application sites (soil and leaf). The use of boron instock plants improves the root system of plants from cuttings, the most efficient foliar application than the soil. The application of this micronutrient promotes balance between root / shoot, ensuring the formation of a balanced changes, given that the leaf supply increases the volume of the stake roots. Therefore the supply of boron to headquarters makes the process effectively, reducing cost, optimizing time and assuring the quality of fruit seedlings.

O cultivo de nêsperas vem aumentando no Brasil e no mundo, sendo uma importante fonte de renda para pequenas propriedades, no entanto, a produção de mudas pode ser um gargalo de sua expansão. Dessa forma o objetivo do presente trabalho foi avaliar o reflexo do boro na qualidade das mudas de nespereira, bem como o local de seu fornecimento às plantasmães determinando-se o modo de aplicação mais eficiente neste processo. Foram utilizadas quatro doses de boro (0; 2,5; 5,0 e 7,5 mg dm-3 ) e dois locais de aplicação (no solo e foliar). A utilização de boro nas plantas-matrizes melhora o sistema radicular das mudas obtidas por estaquia, sendo a aplicação foliar mais eficiente do que via solo. A aplicação deste micronutriente promove o equilíbrio entre raiz/parte aérea, garantindo a formação de uma muda equilibrada, haja vista que o fornecimento foliar aumenta o volume de raízes da estaca. Portanto o fornecimento de boro às matrizes torna o processo eficaz, reduzindo custo, otimizando tempo e garantindo a qualidade das mudas frutíferas.
Dosages and modes of application of boron in the production of seedlings loquat tree
Keywords: Eriobotrya japonica Lindl; Estaquia; Micronutriente; Propagação vegetativa; Cutting; Micronutrient; Vegetative propagation